NEWSPAPER COVERAGE OF WOMEN`S PARTICIPATION IN ENTREPRENEURSHIP: ANALYSIS OF DAILY TRUST AND GUARDIAN NEWSPAPERS (Journal of the Management Sciences, 2025)
Women's participation in entrepreneurship and business activities in Nigeria significantly contributes to the nation’s economic, agricultural, and food production growth. However, their efforts remain underrepresented in the media compared to their male counterparts. Media coverage tends to highlight women entrepreneurs only when they are prominent public figures, while the majority of women making substantial contributions to national development receive little attention. This study examines the coverage of women’s participation in entrepreneurship in Daily Trust and The Guardian newspapers. Anchored on the agenda-setting theory, the study adopts content analysis to assess the frequency, prominence, and framing of reports related to women entrepreneurs in the selected newspapers. Findings reveal that women’s participation in entrepreneurship is largely underreported and accorded minimal prominence compared to other business-related issues. The study recommends that media organizations should enhance the visibility and representation of women entrepreneurs by giving adequate publicity, priority, and prominence to their stories. Such efforts can encourage greater women participation in entrepreneurship and attract support from both governmental and non-governmental bodies
Keywords: Media, Newspaper Coverage; Women; Entrepreneurship; Participation